2011
DOI: 10.1007/s00784-011-0563-6
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis affects the proliferation and differentiation of ovine osteoblast-like cells

Abstract: Enterococcus faecalis (E. faecalis) is a Gram-positive bacterium, mostly recovered from root-filled teeth with persistent periapical lesions. Bacterial contamination of root canals inevitably results in interaction between E. faecalis and periapical tissues during the dynamic process of periapical inflammation. This study investigated the impact of heat-inactivated endodontic E. faecalis on the proliferation and the differentiation of ovine osteoblast-like cells, in an attempt to elucidate its putative enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(42 reference statements)
1
9
0
1
Order By: Relevance
“…Our study showing the inhibition of osteoblast differentiation by HKEF is in keeping with a previous study that E. faecalis decreased mineralization in ovine osteoblast-like cells (27). In fact, this inhibition of osteoblast differentiation may not be restricted solely to E. faecalis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showing the inhibition of osteoblast differentiation by HKEF is in keeping with a previous study that E. faecalis decreased mineralization in ovine osteoblast-like cells (27). In fact, this inhibition of osteoblast differentiation may not be restricted solely to E. faecalis.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, it was reported that bacterial adherence to the host cells and their virulence were not affected by heat treatment to the bacteria (27,33). Although the HKEF has been widely used in the studies on bacterial pathogenesis and host immunity (2, 34), HKEF may not be identical with live E. faecalis in the interaction with and influence on host cells.…”
Section: Discussionmentioning
confidence: 97%
“…The present study revealed the inhibitory effect of E. faecalis on the proliferation and differentiation of murine pre-osteoblasts. Similarly, Karygianni et al (2012) reported the negative effect of E. faecalis on the proliferation and differentiation of ovine osteoblast-like cells (Karygianni et al 2012). Bone mineralization is attributable to the deposition of phosphate, calcium and organic matrix (Hill 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Karygianni et al . () reported the negative effect of E. faecalis on the proliferation and differentiation of ovine osteoblast‐like cells (Karygianni et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation